Structures of vertebrate Patched and Smoothened reveal intimate links between cholesterol and Hedgehog signalling. (August 2019) - Kowatsch, Christiane; Woolley, Rachel E; Kinnebrew, Maia; Rohatgi, Rajat; Siebold, Christian
Highlights: Recently determined cryo-EM structures of the HH receptor PTCH1 have provided detailed insights into the receptor–ligand (PTCH1–SHH) interaction, highlighting the importance of the SHH palmitoyl- and cholesterol modifications in PTCH1 inactivation. Multiple sterol binding sites in all the PTCH1 structures define a potential transport path across the lipidic bilayer. Multiple ligand binding sites have been found in all SMO crystal structures: a canonical TMD binding site and a hydrophobic groove in the CRD can both bind sterol molecules. Cholesterol and oxysterols can bind and activate SMO, suggesting that PTCH1 regulates SMO by restricting its access to a sterol ligand. Abstract : The Hedgehog (HH) signalling pathway is a cell–cell communication system that controls the patterning of multiple tissues during embryogenesis in metazoans. In adults, HH signals regulate tissue stem cells and regenerative responses. Abnormal signalling can cause birth defects and cancer. The HH signal is received on target cells by Patched (PTCH1), the receptor for HH ligands, and then transmitted across the plasma membrane by Smoothened (SMO). Recent structural and biochemical studies have pointed to a sterol lipid, likely cholesterol itself, as the elusive second messenger that communicates the HH signal between PTCH1 and SMO, thus linking ligand reception to transmembrane signalling.